Consensus of Criteria Ranking in Women's Decision-making - Ab. Ghani, Puzziawati; Jemain, Abdul Aziz (Universiti Putra Malaysia Press, 2005)
This paper investigates the nine criteria often weighed by working women in their decision-making. Four methods of deriving weight for each criterion are applied. Each method used will produce different weight values. In this paper we are going to suggest a way to reconcile the differences in order to get a consensus. For that purpose, ordered weighted average with fuzzy quantifier will be employed. As an illustration, a set of data collected from 340 women, academic and support staff of Universiti Teknologi MARA in Shah Alam, will be utilised. Ratings of importance of each criterion by these women were obtained through a set of questionnaires. The nine criteria used are also presented in this paper.